Worst-Case Execution Time Analysis of Mixed Critical Applications on Multicore Systems - Godabole, Preeti; Bhole, G. P. (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Multicore technology, which has previously been effective in general-purpose computers, is now making inroads into embedded systems. While this improves performance, it also raises the question of how to distribute software activities to the hardware platform's cores, because different allocations have varied added functional features. With the use of multicores, the tasks’ execution time varies in an unpredictable fashion. Many scheduling problems in autonomous cars and avionics systems are mixed critical as they comprise tasks at different critical levels. The primary purpose of this research is worst-case execution time analysis and system makespan evaluation of fault-tolerant mixed critical applications. The study considers priority-based task scheduling algorithms for multicore critical systems. The work has considered distinct parameters of evaluation namely deviation in actual execution time, system makespan, and fault- tolerance. The experimentation on a real-time kernel indicates, that GEDF has minimal deviation of only 4.6% in the execution times as compared to PEDF which is 15.8% when active backups of high critical tasks are added to the system. The global approach outperforms the partitioned approach for the considered parameters in a mixed-critical application.